2020
DOI: 10.3171/2020.9.focus20537
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery training in India during the COVID-19 pandemic: straight from the horse’s mouth

Abstract: OBJECTIVEThe COVID-19 pandemic has forced medical professionals throughout the world to adapt to the changing medical scenario. The objective of this survey was to assess the change in neurosurgical training in India following the COVID-19 pandemic.METHODSBetween May 7, 2020, and May 16, 2020, a validated questionnaire was circulated among neurosurgical residents across India by social media, regarding changes in the department’s functioning, patient interaction, surgical exposure, changes in academics, and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
(44 reference statements)
1
35
1
Order By: Relevance
“…3 We conducted a nationwide survey of neurosurgical residents in India, from 7 to 16 May 2020, with 118 respondents from various phases of training, spanning the length and breadth of the country. 4 We found results very similar to those of Wittayanakorn et al., though a few key differences are apparent. Most respondents (88.1%) in our study worked in institutions that dealt with both COVID-19 and non-COVID-19 patients.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…3 We conducted a nationwide survey of neurosurgical residents in India, from 7 to 16 May 2020, with 118 respondents from various phases of training, spanning the length and breadth of the country. 4 We found results very similar to those of Wittayanakorn et al., though a few key differences are apparent. Most respondents (88.1%) in our study worked in institutions that dealt with both COVID-19 and non-COVID-19 patients.…”
supporting
confidence: 88%
“…Academic activities, too, have taken a hit, with almost three-fourths of our respondents reporting hampering of their research/thesis, 4 compared with one-third as reported by Wittayanakorn et al. 1 The number of academic sessions conducted by neurosurgery departments in India have decreased by 32.60%, from a median of 5 per week to 2 per week ( P = 0.000).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…They reported that their residents logged in an average of 15 (58%) and 5 (20%) fewer cases in April 2020 and May 2020, respectively, and this result was statistically significant. In a nationwide survey conducted among 118 neurosurgery residents from India from May 7, 2020, to May 16, 2020, 28 we observed a significant decline of 67.5% in the surgical exposure of residents since the onset of the pandemic, with the average number of surgeries performed by a resident decreasing from 39.9 to 12.3 per month ( P = 0.000). In addition, three fourths of respondents reported hampering of research activities, and the number of academic sessions had decreased by 32.6% from a median of 5 per week to 2 per week ( P = 0.000).…”
mentioning
confidence: 84%
“…We must rise above the challenge and again attempt to resume work with the necessary precautions. 15 Proper evidence-based protocols, creation of adequate COVID-19 testing facilities, and the provision of ample personal protective equipment have been instrumental in restarting nonemergent surgeries in our experience.…”
mentioning
confidence: 99%